The dark and not so humble: School-type effects on the Dark Triad traits and intellectual humility. (1st September 2020) - Cannon, Michael; Vedel, Anna; Jonason, Peter K.
Abstract: The Dark Triad traits (i.e., narcissism, psychopathy, and Machiavellianism) are strongly associated with organizational misbehavior, and some argue that high levels of these traits in the corporate and financial elite are causing the corporate scandals exposed and ever present in the media. Individuals high in the Dark Triad traits are indeed more likely than others to select academic majors suited for corporate careers (e.g., business). However, individuals characterized by the Dark Triad traits may have particular educational trajectories starting before university. We compared ( N  = 924) rates of the Dark Triad traits in those who went to (British) private schools and state schools and how this might lead to individual differences in intellectual humility and academic performance. Privately educated students had higher Dark Triad trait scores than state-schooled students. Also, privately educated students had less intellectual humility and poorer academic performance than state-schooled students. There was a negative relationship between the Dark Triad traits and intellectual humility, and this relationship was stronger for privately schooled students. Furthermore, the Dark Triad traits mediated the relationship between participant's schooling and intellectual humility and also mediated the relationship between participant's sex and intellectual humility. Highlights: Privately schooled students were higher on the Dark Triad traits and less humble. Men were also higher on the Dark Triad traits and lower on intellectual humility. Intellectual humility was negatively correlated with the Dark Triad traits. Academic performance was positively correlated with intellectual humility.